Reaping the benefits of global value chains in Turkey - Ziemann, Volker (OECD Economics Department Working Papers, 2017)
Despite major progress, Turkey still lags behind most comparable countries in terms of exported value added per capita. Its remarkable economic performance over the past 15 years has not been sufficiently backed by gains in export market shares, in particular when measured in value added terms. While Turkey incorporates an increasing share of foreign value added in its own exports, its capacity to provide intermediate inputs to other countries' exports is still limited. This paper argues that Turkey's participation in global value chains remains below potential owing to institutional features that hamper efficient allocation of capital and labour, obstacles inherent in bilateral trade agreements and entry regulations, underdeveloped human capital and insufficient investment in innovation, R&D and knowledge-based capital. Progress along these dimensions would strengthen Turkey's backward and forward trade linkages and contribute to rebalancing its growth model. The adjustment process towards a more export-oriented economy operating on a level playing field needs to be flanked by dedicated industrial, social and environmental policies to alleviate adverse consequences on displaced firms and workers and the ecosystem